Studies on Schismatoglottideae (Araceae) of Borneo LXIX: Schismatoglottis imbakensis, a new species of the Patentinervia Complex from ultramafic rocks, Sabah - Kartini Saibeh; Peter C. Boyce; Wong, Sin Yeng (University of Florence, 2020)
Schismatoglottis imbakensis is described as a new species of the Schismatoglottis Patentinervia Clade from forested ultramafic rocks, and compared with S. retinervia Furtado, the only the species for the clade yet described from Sabah.